The Use of Voki as A Media to Support the Enhancement of First Grade Students Speaking Skills at SMPN 4 Tambun Selatan - Akhmad Subkhi Ramdani (LPPM Universitas Mohammad Husni Thamrin, 2018)
Speaking skill is very crucial for every human being in order to be able to communicate and deliver his or her thoughts among themselves. However, many people around the world speak in vary languages; it depends on their origin. Consequently, many or most of them do not master or able to speak in those languages. So that, people around the world agreed to use some languages as international languages. These languages used as a medium of communication by people whose native languages are different or not mutually intelligible; people are used to say those languages as Lingua Francas. There are some languages that included in Lingua Francas i..e, English. This research is aimed to investigate and explore the use of VOKI to support the enhancement of first grade students’ speaking skills at SMPN 4 Tambun Selatan, Bekasi. The method used in this research is qualitative approach, and it applied Research and Development technique. In this case, the writer collected the data by using observation, structural interview, questionnaire and documentation. The interview was done for the students of first grade students’ speaking skills at SMPN 4 Tambun Selatan, Bekasi. Based on the result of the research, it was found that there were several factors which influence students’ inabilities to speak in English properly, they were students’ speaking ability was low or poor, time limitation, uncomfortable feeling in learning English, lack of motivation, lack of exposures, insufficient materials, and did not know how to start speaking, and lack of feedback. In addition, it was also found that Voki had some features that could be used to solve those problems of the research, the problems of students in speaking English properly. This research can be concluded that the use of Voki as a media to enhance students’ speaking skills to promote the extensive learning at SLTPN 4 Tambun Selatan is useful. It is proven by several problems that hinder the teaching learning process are solved.